КОНТЕКСТЛИ ТАЪЛИМ АСОСИДА МАТЕМАТИК КОМПЕТЕНТЛИКНИ ШАКЛЛАНТИРИШ - Эрисбаев, С.А. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of ways of forming mathematical competence on the basis of contextual teaching.